Prevalence and Predictors of Left Ventricular Diastolic Dysfunction in Malaysian Patients With Type 2 Diabetes Mellitus Without Prior Known Cardiovascular Disease - Chee, Kok Han; Tan, Kok Leng; Luqman, Ibrahim; Saiful, Shahrizal Shudim; Chew, Yee Yean; Chinna, Karuthan; Tan, Alexander Tong Boon (Frontiers in Cardiovascular Medicine, 2021)
Objective: Existing data showed that left ventricular diastolic dysfunction is common in individuals with type 2 diabetes mellitus (T2DM). However, most of the studies included diabetic patients who have prior cardiovascular disease, which might be the compounding factor for ventricular dysfunction. This study aimed to determine the prevalence and predictors of left ventricular diastolic dysfunction in an Asian population with T2DM without prior cardiovascular disease using the latest recommended echocardiographic assessment for left ventricular diastolic dysfunction. Design and Participants: This is a cross-sectional study in which eligible patients with T2DM without history of coronary artery disease, heart failure, or valvular heart disease were recruited. Demographic data, diabetic control, comorbidities, microvascular/macrovascular complications, and medications prescribed were recorded. Venous blood was sent to test for B-type natriuretic peptide, and transthoracic echocardiography was performed to assess left ventricular dysfunction. Setting: This study was performed in a tertiary healthcare center located in Kuala Lumpur, Malaysia. Results: Of the 301 patients, 83.1% have had T2DM for >10 years, with 45.8% being poorly controlled. Comorbidities include hypertension (77.1%), hyperlipidemia (91.0%), and pre-obesity/obesity (72.9%). Majority had absence of microvascular (albuminuria, retinopathy, and neuropathy) and macrovascular (peripheral vascular disease and stroke) complications. None had raised B-type natriuretic peptide levels, and 93.7% had no symptoms of heart failure. On echocardiographic assessment, 70.1% had left ventricular diastolic dysfunction, and 90.5% had Grade 1/mild severity. Age, ethnicity, insulin therapy, presence of hypertension, and hyperlipidemia were significantly associated with left ventricular diastolic dysfunction. Older T2DM patients of Chinese ethnicity and on insulin are about two times more likely to develop left ventricular diastolic dysfunction. Conclusion: There was a high prevalence of asymptomatic left ventricular diastolic dysfunction among patients with T2DM without prior known cardiovascular disease. Older age, insulin therapy, and Chinese ethnicity were risk factors for left ventricular diastolic dysfunction in T2DM.